Immersive Experiences in Virtual Science Labs: A Systematic Review and the VIRTAS Framework - Anis Ezzaty, Mohd Saidi; Syahrul Nizam, Junaini; Wan Azani, Mustafa (2025)
Virtual laboratories and Metaverse platforms are reshaping science education by offering immersive, interactive, and scalable alternatives to traditional labs. This systematic review synthesizes 37 peer-reviewed studies (2021–2024) from Scopus and Web of Science, guided by PRISMA protocols. Findings show that Augmented and Virtual Reality-based virtual labs enhance understanding of abstract scientific concepts, promote critical thinking, and support collaborative problem-solving through real-time simulations and feedback. These technologies improve access to practical science experiences, especially in under-resourced contexts. Key challenges persist, including digital inequality, cognitive overload, and limited teacher preparedness. To address these, the review proposes a new framework: Virtual Immersion for Real-Time Thinking, Access, and Skills (VIRTAS). It is built on six pedagogical pillars based on the SLR results: immersive simulation, instant feedback, gamified learning, team collaboration, equitable access, and skill scaffolding. Anchored in Theory, Context, Construct and Methods (TCCM) analysis, VIRTAS offers a model for designing and assessing Metaverse-based science labs. The review outlines a roadmap for future research, policy, and practice in immersive Science, Technology, Engineering, and Mathematics (STEM) education.